Caste: Its Twentieth Century Avatar - Srinivas,M.N.ed (Viking, 1996)
As India attempts to modernize and ready itself for the twenty-first century, the issue of caste takes on an overwhelming importance. What form does caste take today? How can its debilitating aspects be countered? This book, edited and introduced by one of India's most eminent sociologists, attempts to answer these and other crucial questions. The essays in this volume, each authored by an expert on the subject, include a stimulating assessment of the role of women in perpetuating caste; incisive analyses of the relationship between caste and the economy, and between caste and Hinduism; a review of the backward class movements in Tamil Nadu; a commentary on the power struggle in UP and Bihar amongst the backward castes; the relationship between efficiency and job reservation; observations on caste amongst Muslims and Christians in India and critiques of the Mandal Commission Report and the Mandal judgement.